Annotated checklist of the flat bug family Aradidae Brullé, 1836 from East Africa (Hemiptera, Heteroptera) - Heiss, Ernst (Zootaxa, 2013)
The flat bug fauna of East African countries has never been the subject of a comprehensive study. Most descriptions and distribution data are from colonial times, with most records coming from what is present day Tanzania, Rwanda and Burundi. In this checklist, the data from all available literature was assembled, and references are given for 16 genera and 37 species.